2011
DOI: 10.1186/1471-2229-11-143
|View full text |Cite
|
Sign up to set email alerts
|

Parthenocarpic potential in Capsicum annuumL. is enhanced by carpelloid structures and controlled by a single recessive gene

Abstract: BackgroundParthenocarpy is a desirable trait in Capsicum annuum production because it improves fruit quality and results in a more regular fruit set. Previously, we identified several C. annuum genotypes that already show a certain level of parthenocarpy, and the seedless fruits obtained from these genotypes often contain carpel-like structures. In the Arabidopsis bel1 mutant ovule integuments are transformed into carpels, and we therefore carefully studied ovule development in C. annuum and correlated aberran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
3
21
0
2
Order By: Relevance
“…The tomato gene S1ARF7, expressed in unpollinated mature ovaries, was shown to be a negative regulator of fruit set prior to pollination and fertilization and to moderate the auxin response during fruit growth (de Jong et al 2009). In Capsicum, parthenocarpy appeared to be controlled by a single recessive gene (CaARF8); however, no variation in the coding sequence was observed in CaARF8 (Tiwari et al 2011). Another study demonstrated that silencing the tomato SlAux/IAA9 gene could induce parthenocarpic fruit initiation (Wang et al 2005).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The tomato gene S1ARF7, expressed in unpollinated mature ovaries, was shown to be a negative regulator of fruit set prior to pollination and fertilization and to moderate the auxin response during fruit growth (de Jong et al 2009). In Capsicum, parthenocarpy appeared to be controlled by a single recessive gene (CaARF8); however, no variation in the coding sequence was observed in CaARF8 (Tiwari et al 2011). Another study demonstrated that silencing the tomato SlAux/IAA9 gene could induce parthenocarpic fruit initiation (Wang et al 2005).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Though intrinsic mechanism of natural parthenocarpy in plants is still unresolved, it is observed that natural parthenocarpic fruits such as banana (Khalifah, 1966) and mandarin (Talon et al, 1990, 1992) record increase in auxin and gibberellins level while levels of ABA declines (Talon et al, 1990). Genetically, parthenocarpy may happen due to a single partially dominant gene as in cucurbits (Kim et al, 1992; Menezes et al, 2005) or due to a single recessive gene as in sweet pepper (Tiwari et al, 2011) or due pleiotropy of major and minor genes as in brinjal/eggplant (Miyatake et al, 2012). In case of banana, parthenocarpy is hypothesized (Sardos et al, 2016) to be due to a major dominant gene ( P or P1 ) interacting with minor ones (Simmonds, 1953).…”
Section: Parthenocarpymentioning
confidence: 99%
“…In many pepper cultivars (Capsicum annuum L.), a low night temperature induces parthenocarpy (Rylski, 1973;Tarchoun et al, 2003;Tiwari et al, 2011). However, in such cultivars, the unpollinated parthenocarpic fruit set is lower than that of pollinated fruit, especially in the absence of low night temperatures.…”
Section: Introductionmentioning
confidence: 99%